Comparison Analysis Of Alternative Design And Budget Plan Using Steel Structure With Concrete Structure For Dormitory Of PMY Construction Project In Baucau, Timor-Leste - Julystiana Tistogondo; Emilia Belo (Journal of World Conference (JWC), 2020)
Re-design steel structure with concrete structure for dormitory of PMY Baucau building with floor plan size , consisting of the 2 floors with high aimed to: 1.) to Design the dimension of the upper concrete structure such as column, beam and plate with Preliminary design, 2.) to Calculate the gravity and seismic plan load that works for the building, 3.) to determine the formation of beam and column reinforcement from the analysis result by using the Frame System of Specific Moment Beares (SRPMK). The structure analysis was conducted using the SAP2000.V14, 4.) to Comparing Budget Plan between upper steel structure and upper concrete structure to discover economic value between those two upper structures. Calculation of concrete structure refers to SNI 2847-2013 , calculation of equivalent static earthquake refers to SNI 1726-2012 and calculation of Budget plan for labour and material prices from Timor-Leste. Final calculation of dimension for the concrete structure from preliminary design are : Beam and , Column and Plate for ground and first floor. And the final cost estimation for concrete structure around and steel structure around , those two structure show that concrete structure is economical than steel structure.